IS200/IS605 family single-strand transposition: mechanism of IS608 strand transfer - He, Susu (Oxford University Press, 2013)
Transposase, TnpA, of the IS200/IS605 family member IS608, catalyses single-strand DNA transposition and is dimeric with hybrid catalytic sites composed of an HUH motif from one monomer and a catalytic Y127 present in an α-helix (αD) from the other (trans configuration). αD is attached to the main body by a flexible loop. Although the reactions leading to excision of a transposition intermediate are well characterized, little is known about the dynamic behaviour of the transpososome that drives this process. We provide evidence strongly supporting a strand transfer model involving rotation of both αD helices from the trans to the cis configuration (HUH and Y residues from the same monomer). Studies with TnpA heterodimers suggest that TnpA cleaves DNA in the trans configuration, and that the catalytic tyrosines linked to the 5′-phosphates exchange positions to allow rejoining of the cleaved strands (strand transfer) in the cis configuration. They further imply that, after excision of the transposon junction, TnpA should be reset to a trans configuration before the cleavage required for integration. Analysis also suggests that this mechanism is conserved among members of the IS200/IS605 family.